Role of Secondary Intention Healing - Ward, P. Daniel; London, Nyall; Collar, Ryan (Facial Plastic Surgery, 2013)
Secondary intention wound healing is a simple, yet powerful tool in facial reconstruction. Considered as the most elementary form of wound reconstruction, it is often unused because of concern about the predictability of the result and the desire for immediate reconstruction. Secondary intention wound healing can successfully be used for reconstruction of defects for patients who may not be candidates for involved surgical procedures and should be considered an ideal form of reconstruction for certain defects. In general, superficial defects located in concave areas lead to the best results. Proper wound care, including keeping the wound clean and moist, is a simple, but important, aspect of result optimization. Avoiding the use of secondary intention healing on facial anatomic sites known to produce poor results minimizes complications. Complications encountered may include ectropion, nasal obstruction, alar retraction, alopecia, and poor cosmesis.
Keywords: facial reconstruction; secondary intention; wound healing